Edukasi Pemanfaatan Buah dan Rempah Toga Sebagai Bahan Dasar Pembuatan Infused Water Untuk Detoksifikasi Tubuh di SMK N 2 Rangkas Bitung - Maulana, Ilham; Ardillah, Destry; Irawan, Olgi; Gulo, Triss Ella Julita; Alwia, Nisa; Lubis, Martinasari (Welfare : Jurnal Pengabdian Masyarakat, 2023)
The problem of climate change is causing a decline in public health, so by paying attention to this as a government partner, the Pharmacy S1 Study Program Department has the responsibility to participate in educating the use of fruit, spices, and toga as body detoxification. Infused water is a drink consisting of water enriched with added flavors and nutrients from natural ingredients such as fruits, vegetables, and spices. The purpose of this activity is to provide education to the public on how to maintain health in the face of increased rainfall and extreme climate change by consuming infused water. The method used in this activity is to provide education about making infused water and distributing infused water products made by the service team to students of SMK N 2 Rangkas Bitung. The result of this service is that the students of SMK N 2 Rangkas Bitung know how to make infused water and are equipped with bottles and infused water products to practice directly.